Evaluation of LUTS of the filling phase after Aquablation: A prospective single center experience - De Cillis, Sabrina; Amparore, Daniele; Quarà, Alberto; Checcucci, Enrico; Piana, Alberto; Volpi, Gabriele; Piramide, Federico; Sica, Michele; Ortenzi, Michele; Manfredi, Matteo; Di Dio, Michele; De Luca, Stefano; et al. (Frontiers in Urology, 2022)
Introduction This study aims to assess our first clinical experience with Aquablation in terms of perioperative and 1-year micturition outcomes, with a focus on postoperative lower urinary tract symptoms (LUTS). Materials and methods From 10/2018 to 07/2021, patients referred to our center with BPH-related LUTS, International Prostate Symptom Score (IPSS) ≥10, maximum urinary flow rate (Qmax) ≤12 ml/s, and prostate volume <80 ml were enrolled in this prospective study to undergo Aquablation. Demographics, perioperative data, and complications (according to the Clavien–Dindo system) were collected. Functional outcomes were assessed at 1, 3, 6, and 12 months with IPSS, IPSS quality of life (IPSS QoL), uroflowmetry, and evaluation of post void residue (PVR). The types of LUTS were classified on the basis of IPSS single question answers in filling phase LUTS and voiding phase LUTS. Results Sixty patients were enrolled in the study. The mean patient age was 64.9 ± 7.3 years, prostate volume was 63.5 ± 16.8) ml, Qmax was 8.4 ± 2.6 ml/s, the median (IQR) IPSS was 23 (19–26), and the IPSS QoL score was 5 (4–5). The mean Qmax at 1, 3, 6, and 12 months was 21.1 ± 11, 18.1 ± 5.4, 17.1 ± 6, and 17.8 ± 6.6 ml/s, respectively. The median IPSS urinary symptom score was 2 (2–5) one year after surgery. In parallel, the median IPSS QoL score and mean PVR reached 1 (0–1) and 23.6 ml (25.5) in the 12th month. At 1- and 3-month follow-up, filling phase symptoms were predominant in almost two-thirds of the study population. Within the patients who reported a prevalence of filling phase symptoms at 3 months, 27 of 38 (71%) reported a de novo onset of these symptoms after surgery. Conclusion Aquablation is a safe procedure for treating BPH-related LUTS, and it has been demonstrated to be effective up to 12 months after the procedure. LUTS of the filling phase were more prevalent than voiding phase ones in the first 3 months following surgery, but showed a self-limited fashion.